2020
DOI: 10.18502/jfqhc.7.4.4843
|View full text |Cite
|
Sign up to set email alerts
|

Causes, Patterns, and Economic Implications of Carcass Condemnation of Cattle Slaughtered at Oshana Region, North of Namibia Based on Post-Mortem Inspection

Abstract: Background: Meat inspection is one of the essential tools for ensuring good quality and safe meat. The objective of this study was to evaluate carcass condemnation of cattle slaughtered in Oshana region, North of Namibia. Methods: In this 4-year retrospective study, causes, patterns, and economic implications of carcass condemnation of cattle slaughtered in Oshana region, North of Namibia were evaluated based on post-mortem inspection procedure. The SPSS software version 25 was used for statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to reviewed data, bovine tuberculosis, among all the causes, displayed the highest rate of carcass condemnation for some authors [ 43 , 50 ]. Other causes of cattle carcass condemnation in more than 30% of cases were malignant lymphoma, multiple abscess, septicemia, bruising, or pneumonia [ 39 , 51 ]. Although these results are difficult to interpret, the high rates of condemnation related to bovine tuberculosis and malignant lymphoma could be associated with the absence of eradication programs.…”
Section: Surveillance Of Livestock Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to reviewed data, bovine tuberculosis, among all the causes, displayed the highest rate of carcass condemnation for some authors [ 43 , 50 ]. Other causes of cattle carcass condemnation in more than 30% of cases were malignant lymphoma, multiple abscess, septicemia, bruising, or pneumonia [ 39 , 51 ]. Although these results are difficult to interpret, the high rates of condemnation related to bovine tuberculosis and malignant lymphoma could be associated with the absence of eradication programs.…”
Section: Surveillance Of Livestock Diseasesmentioning
confidence: 99%
“…The presence of bruising on the carcass has been described as a welfare indicator both for pre-slaughter and abattoir operations [ 63 ]. Although bruises represent a negative economic impact related to partial condemnations, total carcass condemnation is really scarce [ 51 ].…”
Section: Surveillance Of Livestock Diseasesmentioning
confidence: 99%
“…The latter observed that carcasses were processed on bare ground, meats were washed with water from the gutters and effluents channelled to nearby natural water bodies, which may be sources of drinking water for the communities around the abattoirs [11,72,96,97]. Outside Nigeria, poor sanitary conditions of SHs and condemnation of meats due to various disease conditions have be reported in South Africa [98,99], Ethiopia [100], Iran [101], Tanzania [102], Namibia [103] and Kenya [104].…”
Section: Table 5 Association Between Geographical Location Of Slaught...mentioning
confidence: 99%